New Approach to Accelerated Image Annotation by Leveraging Virtual Reality and Cloud Computing - Guérinot, Corentin; Marcon, Valentin; Godard, Charlotte; Blanc, Thomas; Verdier, Hippolyte; Planchon, Guillaume; Raimondi, Francesca; Boddaert, Nathalie; Alonso, Mariana; Sailor, Kurt; Lledo, Pierre-Marie; Hajj, Bassam; et al. (Frontiers in Bioinformatics, 2022)
Three-dimensional imaging is at the core of medical imaging and is becoming a standard in biological research. There is an increasing need to visualize, analyze and interact with data in a natural three-dimensional context. By combining stereoscopy and motion tracking, commercial virtual reality (VR) headsets provide a solution to this important visualization challenge by allowing any user to view volumetric image stacks in a highly intuitive fashion. While optimizing the visualization and interaction process in VR remains an active topic, one of the most pressing issues is how to utilize VR for annotation and analysis of data. Annotating data is often a required step for training machine learning algorithms. For example, enhancing the ability to annotate complex three-dimensional data in biological research is necessary as newly acquired data may come in limited quantities. Similarly, medical data annotation is often time-consuming and requires expert knowledge to identify structures of interest correctly. Moreover, simultaneous data analysis and visualization in VR is computationally demanding. Here, we introduce a new procedure to visualize, interact, annotate and analyze data by combining VR with cloud computing. VR is leveraged to provide natural interactions with volumetric representations of experimental imaging data. In parallel, cloud computing performs costly computations to accelerate the data annotation with minimal input required from the user. We demonstrate multiple proof-of-concept applications of our approach on volumetric fluorescent microscopy images of mouse neurons and tumor or organ annotations in medical images.